Diversity and phylogenetic relationship of cellulolytic bacteria from the feces of Bali Cattle in South Central Timor, East Nusa Tenggara, Indonesia - HILDEGARDIS MISSA; ARI SUSILOWATI; RATNA SETYANINGSIH (Biodiversitas Journal of Biological Diversity, 2016)
Missa H, Susilowati A, Setyaningsih R. 2016. Diversity and phylogenetic relationship of cellulolytic bacteria from the feces of Bali Cattle in South Central Timor, East Nusa Tenggara, Indonesia, Indonesia. Biodiversitas 17: 614-619. There are three types of cattle farms with different kinds of feed in South Central Timor, that are maintained around Supul Lake, quarantined and left in the wild. This research aims to isolate, identify and determine the genetic relationship among of cellulolytic bacteria from the feces of Bali Cattle (Bos javanicus javanicus DÂ´Alton, 1823, syn. Bos javanicus sondaicus Temminck, 1839/Blyth, 1842) in South Central Timor. Theisolation of cellulolytic bacteria was done by using spread plate method on Carboxymethyl Cellulose (CMC) media. Cellulolyticactivities were determined by the clear zone visibility using 0.1% congo red indicator. 16S rRNA encoding genes amplification wasconducted using Polymerase Chain Reaction (PCR) using 63F and 1387r primers. Sequences of the 16S rRNA encoding genes were analyzed by bioinformatics using Nucleotide BLAST on NCBI website to determine the species of bacteria based on sequencesimilarity. The construction of the phylogenetic tree of cellulolytic bacteria was done using MEGA 7.0 software. The results were 48isolates showing cellulase activity. There were 12 isolates from Supul Lake which have high cellulase activity namely: S1H6, S2H5 S2H7 S3H; in quarantine location: K1H6, K2H3, L2H7, K2H4, K1H2, K3H2; and in wild care system: L1H4 and L1H5. These activities were presented in clear zone about 7.08 to 1.47 cm. Based on the analysis of 16S rRNA encoding genes, there were 5 different genera found in 12 isolates with high cellulolytic activity. The isolates possessed similarity with Pseudomonas sp. 96%, Acinetobacter sp. 95%, Bacillus 97%, Stenotrophomonas 88%, and Brachybacterium sp. 97%. There were seven bacterial isolates having the potential to be declared as new bacterial species with <97% similarity percentage that are SIH6, S2H5, K2H3, K2H4, LIH4, LIH5, L2H7. Based on the phylogenetic tree cellulolytic bacteria showed the closest genetic relationship of 0.0% and farthest of 19.3% L2H7 isolate with Brachybacterium sp. S21F1